2020
DOI: 10.1186/s00015-020-00361-7
|View full text |Cite
|
Sign up to set email alerts
|

Messinian or Pleistocene valley incision within the Southern Alps

Abstract: Many of the valleys on the southern slope of the Alps are over-deepened, having bedrock valley floors well below sea level. This has typically been attributed to incision that occurred during the Messinian Salinity Crisis (MSC) when sea level dropped by hundreds of meters, leading to incision of many of the margins of the Mediterranean. We reassess this interpretation by documenting the correct elevation of the valley floor of the Adige river, one of the major valleys draining the Southern Alps, and by estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 52 publications
4
18
0
Order By: Relevance
“…In this paleo-landscape, the valleys separating different geological domains (Adamello, Tonale, Brenta) were likely not as deeply entrenched as today, allowing an efficient transfer of sediment from the north-west to south-east across major tectonic lineaments, partially by fluvial systems and occasionally by glaciation events. This observation is consistent with recent studies (Winterberg et al, 2020) showing that major river valleys in inner parts of the Southern Alps (i.e., Adige Valley) were not all yet deeply carved during the Messinian sea-level drawdown.…”
Section: Implications For Paleogeography and Tectonic Evolutionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this paleo-landscape, the valleys separating different geological domains (Adamello, Tonale, Brenta) were likely not as deeply entrenched as today, allowing an efficient transfer of sediment from the north-west to south-east across major tectonic lineaments, partially by fluvial systems and occasionally by glaciation events. This observation is consistent with recent studies (Winterberg et al, 2020) showing that major river valleys in inner parts of the Southern Alps (i.e., Adige Valley) were not all yet deeply carved during the Messinian sea-level drawdown.…”
Section: Implications For Paleogeography and Tectonic Evolutionsupporting
confidence: 93%
“…These clues open intriguing questions that could be refined by future studies, especially if other allochtonous sediments would be identified in other caves of Brenta. For example a Miocene fluvial-glacial interconnection between different areas of the Alps (Brenta-Adamello-Tonale) suggest that the Messinian Salinity Crisis sea-level drop and related accelerated fluvial erosion may not have reached the internal most elevated region of the Southern Alps (Winterberg et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is generally in good agreement with observations in other perialpine lakes north of the Alps (e.g., Finckh et al, 1984;Preusser et al, 2010;Fabbri et al, 2018). While the Southern Alpine deep incision (Finckh, 1978) may be caused either by subglacial activity (Winterberg et al, 2020) or by the Messinian drawdown of base level (e.g., Cazzini et al, 2020), overdeepenings north of the Alps are primarily attributed to a glacial origin (Preusser et al, 2010). During the Last Glacial Maximum (LGM), the Rhine Glacier's ice elevation above the Lake Constance area was at ∌1,000 m a.s.l (Bini et al, 2009), indicating an ice thickness of ∌1,500 m. During the Quaternary, several glacial advances coupled with the erosive power in the subglacial domain created overdeepenings and shaped the perialpine realm (Preusser et al, 2010;Reber and Schlunegger, 2016;Magrani et al, 2020).…”
Section: Bedrock Morphology and Overdeepeningsupporting
confidence: 90%
“…The study site is located within the NNE-SSW-oriented Lake Garda valley. This valley is linked to the tectonic evolution of the Giudicarie fault [32,33], while its depth is related to the Messinian sea level drop [34][35][36]. Lake Garda and the lower Sarca Valley are affected by present-day tectonic deformation [19,37,38], and earthquakes with an equivalent magnitude of M e = 5 are common in the region [39].…”
Section: Geographical Settingmentioning
confidence: 99%
“…The aim of our study was to clarify whether the Gorte deposits were formed during a single event or during several events, as proposed by [28,29]. We used a multi-method approach combining field surveys supported by remote imagery, cosmogenic 36 Cl exposure dating and numerical runout modeling to reconstruct the large slope failures and the emplacement dynamics. Our new data can be compared with nearby isotopically dated deposits, for example, the Marocche di Dro [16], Lavini di Marco [30], Varini [31] and Molveno [12] rock avalanches (Figure 2), which allows an assessment of the most important preconditioning factors and possible triggers in a regional context.…”
Section: Introductionmentioning
confidence: 99%